One-Pot Visual Detection of African Swine Fever Virus Using CRISPR-Cas12a - Qin, Chao; Liu, Jiajia; Zhu, Wenqi; Zeng, Muchu; Xu, Ke; Ding, Jinmei; Zhou, Hao; Zhu, Jianshen; Ke, Yuqing; Li, Lai Yan; Sheng, Gaoyuan; Li, Zhuoru; et al. (Frontiers in Veterinary Science, 2022)
African swine fever virus (ASFV) is a leading cause of worldwide agricultural loss. ASFV is highly contagious and lethal disease for both domestic and wild pigs, has brought enormous economic losses to a number of countries. Conventional methods such as general polymerase chain reaction and isothermal amplification are time-consuming, instrument-dependent, and of unsatisfactorily accurate. Therefore, rapid, sensitive, and field-deployable detection of ASFV is important for disease surveillance and control. Herein, we created a one-pot visual detection system for ASFV with CRISPR/Cas12a technology combined with LAMP or RPA. Mineral oil sealing strategy was adopted to mitigate sample cross-contamination between parallel vials during high throughput testing. Furthermore, the blue fluorescence signal produced by ssDNA reporter could be observed by naked eye without any dedicated instrument. For CRISPR-RPA system, detection could be completed within 40min with advantageous sensitivity. While CRISPR-LAMP system could complete it within 60min with a high sensitivity of 5.8×10^2 copies/μl. Furthermore, we verified such detection platforms display no cross-reactivity with other porcine DNA or RNA viruses. Both CRISPR-RPA and CRISPR-LAMP systems permit highly rapid, sensitive, specific and low-cost Cas12a-mediated visual diagnostic of ASFV for point-of-care testing (POCT) applications.